Characteristics of Virus Symptoms in Chili Plants (Capsicum frutescens) Based on RGB Image Analysis - Asmar Hasan; Widodo Widodo; Kikin Hamzah Mutaqin; Muhammad Taufik; Sri Hendrastuti Hidayat (AGRIVITA, Journal of Agricultural Science, 2022)
Virus infection in chili plants may cause various symptoms. The complexity of the symptoms and human vision ability often become limiting factors during disease investigations. Digital image analysis is expected to become a method to assist in comprehensively describing the symptoms of plant viruses. A disease survey was conducted on cayenne pepper fields in Southeast Sulawesi Province to observe symptoms of virus infection virtually and to record the symptomatic plant using an RGB camera. The split-channel method is used to process images, followed by multidimensional scaling statistical analysis. Later on, viruses associated with plants were detected serologically. Single or mixed infection of Tobacco mosaic virus, Cucumber mosaic virus, Chili veinal mottle virus, and Pepper mottle virus was confirmed by plant leaves showing yellow-mosaic and mottle symptoms. The digital image analysis method could show variations in the characteristics of symptoms based on digital numbers in that cannot be recognized based on the observation of visual symptoms. A new approach to study the interactions between plant infecting viruses and their effects based on image analysis has also been developed during this research. This method needs to be further validated through testing under controlled conditions, such as inoculating plants with a predetermined type of virus.